Report of the NIH Task Force on Research Standards for Chronic Low Back Pain - Deyo, MD, MPH, Richard A.; Dworkin, DDS, PhD, Samuel F.; Amtmann, PhD, Dagmar; Andersson, MD, PhD, Gunnar; Borenstein, MD, David; Carragee, MD, Eugene; Carrino, MD, MPH, John; Chou MD, Roger; Cook PhD, Karon; DeLitto, PT, PhD, Anthony; Goertz, DC, PhD, Christine; Khalsa, DC, PhD, Partap; et al. (International Journal of Therapeutic Massage & Bodywork, 2015)
Despite rapidly increasing intervention, functional disability due to chronic low back pain (cLBP) has increased in recent decades. We often cannot identify mechanisms to explain the major negative impact cLBP has on patients’ lives. Such cLBP is often termed non-specific, and may be due to multiple biologic and behavioral etiologies. Researchers use varied inclusion criteria, definitions, baseline assessments, and outcome measures, which impede comparisons and consensus. The NIH Pain Consortium therefore charged a Research Task Force (RTF) to draft standards for research on cLBP. The resulting multidisciplinary panel recommended using 2 questions to define cLBP; classifying cLBP by its impact (defined by pain intensity, pain interference, and physical function); use of a minimal data set to describe research participants (drawing heavily on the PROMIS methodology); reporting “responder analyses” in addition to mean outcome scores; and suggestions for future research and dissemination. The Pain Consortium has approved the recommendations, which investigators should incorporate into NIH grant proposals. The RTF believes these recommendations will advance the field, help to resolve controversies, and facilitate future research addressing the genomic, neurologic, and other mechanistic substrates of chronic low back pain. We expect the RTF recommendations will become a dynamic document, and undergo continual improvement. Perspective: A Task Force was convened by the NIH Pain Consortium, with the goal of developing research standards for chronic low back pain. The results included recommendations for definitions, a minimal dataset, reporting outcomes, and future research. Greater consistency in reporting should facilitate comparisons among studies and the development of phenotypes.